La Vita S. Pauli Monachi Thebaei di san Girolamo contenuta nel codice manoscritto Vaticanus Latinus 13008 - Degórski, Bazyli (Vox Patrum, 2019)
The essay analyzes the text of the Vita S. Pauli Monachi Thebaei of St. Jerome contained in the Manuscript Code Vaticanus Latinus 13008, kept in the Apostolic Vatican Library. In particular, are indicated and highlighted all variations of the Manuscript differing from the text of the critical edition of this work by St. Jerome (see B. Degórski, Edizione critica della “Vita Sancti Pauli Primi Eremitae” di Girolamo, Institutum Patristicum “Augustinianum”, Roma 1987).